Body mass index and the risk of incident functional disability in elderly Japanese: The OHSAKI Cohort 2006 Study. Issue 31 (August 2016) - Zhang, Shu; Tomata, Yasutake; Sugiyama, Kemmyo; Kaiho, Yu; Honkura, Kenji; Watanabe, Takashi; Tanji, Fumiya; Sugawara, Yumi; Tsuji, Ichiro
Abstract : Abstract: The relationship between the body mass index (BMI) and the incidence of cause-specific disability remains unclear. We conducted a prospective cohort study of 12, 376 Japanese individuals aged ≥65 years who were followed up for 5.7 years. Information on BMI and other lifestyle factors was collected via a questionnaire in 2006. Functional disability data were retrieved from the public Long-term Care Insurance database. BMI was divided into 6 groups (<21, 21–<23, 23–<25, 25–<27[reference], 27–<29 and ≥29). Hazard ratios and 95% confidence intervals for cause-specific disability were estimated using Cox proportional hazards regression models. A U-shaped relationship between BMI and functional disability was observed, with a nadir at 26. The nadir BMI values with the lowest disability risk were 28 for dementia, 25 for stroke, and 23 for joint disease. A low BMI (<23) was a risk factor for disability due to dementia, the HR values (95% CI) being 2.48 (1.70–3.63) for BMI <21 and 2.25 (1.54–3.27) for BMI 21 to <23; a high BMI (≥29) was a risk factor for disability due to joint disease, the HR value (95% CI) being 2.17 (1.40–3.35). There was no significant relationship between BMI and disability due to stroke. The BMI nadirs for cause-specific disability differed: a low BMI (<23) was a risk factor for disability due to dementia, and a high BMI (≥29) was a risk factor for disability due to joint disease. Because BMI values of 23 to <29 did not pose a significantly higher risk for each cause of disability, this range should be regarded as the optimal one for the elderly population. Abstract : Supplemental Digital Content is available in the text